Oromandibular-limb hypogenesis syndrome: a rare case illustrating shortcomings of current classification systems - Small, Lizanne (University of the Free State, 2018)
Background: Oromandibular limb hypogenesis syndrome (OLHS) includes a spectrum of congenital anomalies that affect the mandible, tongue, and maxilla with or without reductive limb anomalies. Their exact aetiology is unknown and most cases occur sporadic. Several syndromes are included under the umbrella of OLHS with considerable overlap in the phenotypical features between them. Two classification systems that of Hall (1971) and Chicarilli (1985) are currently recognised to classify OLHS. Jung et al. proposed a modification of the Chicarilli classification in 2016, but according to the literature this classification has not been used to classify OLHS cases. Case Presentation: A 3 month old male infant presented with clinical features that straddled more than one syndrome as classified under the OLHS. Given the orofacial and extremity malformations of this case it could be classified as Hall Type IIID or VB and Chicarilli Type IV. The aim of this case report was to contribute to understanding the difficulty in the classification of these complex malformations and to review our current classification systems. Conclusion: Shortcomings in the two most commonly used classifications by Hall and Chicarilli was identified and a classification system proposed by Jung et al in 2016 made classification of this case possible as a Jung Type IV D. As a result from this case report it was clear that a review of current classification systems is needed with the aim to establish a single system that will allow for classification for all the subtypes of OLHS.
Dissertation (M.Med. (Plastic and Reconstructive Surgery))--University of the Free State, 2018
Keywords: Oromandibular limb hypogenesis syndrome; Orofacial and limb abnormalities; Hall classification; Chicarilli classification; Jung et al. classification